Maksimalisasi Kepuasan Kerja Melalui Turnover Intention Karyawan Indomaret - IRIANI YUDANINGRUM, BUDI; EKA RAMADHANI, FERRA (STIEKOP MALANG PRESS, 2024)
This research aims to find out that every company must have its own goals to achieve the progress and success of the company itself. To achieve the desired goals, good and proper management is needed to facilitate a company to achieve success. With effective and efficient management, a company can balance everything for the welfare and common goals. If it has achieved common goals, then it is certain that the company will be successful and run well. Based on these objectives, the researcher uses the literature search method and searches for relevant sources. In obtaining the data and information needed, the researcher conducts a literature study first as a consideration and additional insight and requires reference data as a reference for writing.